Government Capacity In Handling Tropical Cyclone Idai Induced Flooding In Chipinge District, Manicland Province, Zimbabwe To Support National Security - Rangarirai Waini; Christine Sri Marnani; Ali Rahmat; Pujo Widodo; Herlina Juni Risma Saragih (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Tropical Cyclone Idai induced flooding hit Zimbabwe from 15-20 March 2019, killing 349 people and damaging infrastructure worthy billions of dollars. Vulnerability to tropical cyclone flood risk remains high against limited government capacity. The Hyogo Framework for Action (2005-2015) indicators were used to analyse government capacity in handling Cyclone Idai disaster. The study used qualitative methodology alongside descriptive research design. Interviews, field observations and document analysis were employed for data collection. Results of the study are: a) legal framework capacity to handle Cyclone Idai met most priority 1 indicators but with some deficiencies, b) early warning systems were satisfactory and fulfilled all priority 2 indicators, c) collaboration and ego-sectoral approach towards building resilience and a safe culture through education, knowledge and innovation fulfilled all priority 3 indicators, d) efforts to reduce flood risk factors met all priority 4 indicators, and e) the active involvement and participation of stakeholders in flood risk research, education and training met all indicators under priority 5 although a holistic disaster response plan has not been developed. Challenges faced were under-funding and inadequate resources, inattention to issues of social vulnerability and social capital, legal gaps and leadership incapacity. Capacity-building efforts implemented were trainings, increased flood risk information dissemination, participation of schools in risk reduction and environmentally friendly conservation measures. The study recommends government to strengthen legal framework, decentralize disaster experts to districts and, allocate adequate funding and resources for risk reduction. Chipinge district to formulate a disaster response plan and institutional structure, increase disaster knowledge through active community engagement and participation in disaster risk reduction to promote resilience for national security stability.